Patterns of EPIYA motifs amongcagA‐positiveHelicobacter pyloristrains: a case–control study in a Turkish population with Eurasian geographical features. Issue 10 (October 2015) - Kocazeybek, Bekir Sami; Caliskan, Reyhan; Cetin, Sibel Erdamar; Ergin, Sevgi; Kuskucu, Mert; Kepil, Nuray; Dinc, Harika Oyku; Erzin, Yusuf Ziya; Saribas, Suat; Tokman, Hrisi Bahar; Kalayci, Fatma; Akgul, Ozer; et al.
Abstract : N/A: Geographical variation in the frequency of various gastroduodenal pathologies was shown to be related to the geographical diversity of H. pylori CagA Glu‐Pro‐Ile‐Tyr‐Ala (EPIYA) patterns. We examined the EPIYA patterns of H. pylori and the association of EPIYA patterns with gastric cancer (GC) for the first time, to the best of our knowledge, in Turkey. The patient group (PG) contained 60 patients [38 GC and 22 duodenal ulcer (DU) patients]. The control group (CG) was 110 individuals [94 gastritis patients and 16 persons with a normal gastrointestinal system (NGIS)]. Specific primers were used for the detection of cagA including empty‐site‐positive and EPIYA‐A, ‐B, ‐C, ‐D PCR. Bands of EPIYA‐A, ‐B, ‐C were confirmed by DNA sequencing. One hundred and forty‐two (83.5 %) strains [60 in the PG (38 GC, 22 DU), 82 in the CG (72 gastritis, 10 NGIS)] were positive for the cagA gene. EPIYA‐C with multiple repeats was detected in 34 (23.9 %) strains, and 22 (64.7 %) were from GC patients. EPIYA‐C with one repeat was detected in 89 (62.7 %) strains, and 54 (60.7 %) were from gastritis patients. EPIYT was detected in 10 strains, and EPIYA‐D was not detected. The number of EPIYA‐C with multiple repeats was significantly higher for the PG than for the CG ( P < 0.0001). In GC patients, the number of EPIYA‐C with multiple repeats was significantly higher than one repeat ( P < 0.0001). In conclusion, our study showed that multiple EPIYA‐C repeats increases the GC risk by 30.6‐fold and the DU risk by 8.9‐fold versus the CG. This indicates that Western‐type H. pylori strains in Turkey have similar EPIYA motifs to those of neighbouring countries and Western populations.